Translumbosacral Neuromodulation Therapy for Fecal Incontinence: A Randomized Frequency Response Trial. (29th January 2021) - Rao, Satish S.C.; Xiang, Xuelian; Sharma, Amol; Patcharatrakul, Tanisa; Yan, Yun; Parr, Rachael; Ayyala, Deepak; Hamdy, Shaheen
Abstract : INTRODUCTION: Treatments for fecal incontinence (FI) remain unsatisfactory because they do not remedy the underlying multifactorial dysfunction(s) including anorectal neuropathy. The aim of this study was to investigate the optimal dose frequency, clinical effects, and safety of a novel treatment, translumbosacral neuromodulation therapy (TNT), aimed at improving neuropathy. METHODS: Patients with FI were randomized to receive 6 sessions of weekly TNT treatments consisting of 600 repetitive magnetic stimulations over each of 2 lumbar and 2 sacral sites with either 1, 5, or 15 Hz frequency. Stool diaries, FI severity indices, anorectal neurophysiology and sensorimotor function, and quality of life were compared. Primary outcome measure was the change in FI episodes/week. Responders were patients with ≥50% decrease in weekly FI episodes. RESULTS: Thirty-three patients with FI participated. FI episodes decreased significantly (∆ ±95% confidence interval, 4.2 ± 2.8 (1 Hz); 2 ± 1.7 (5 Hz); 3.4 ± 2.5 (15 Hz); P < 0.02) in all 3 groups when compared with baseline. The 1 Hz group showed a significantly higher ( P = 0.04) responder rate (91 ± 9.1%) when compared with the 5 Hz group (36 ± 18.2%) or 15 Hz (55 ± 18.2%); no difference was found between the 5 and 15 Hz groups ( P = 0.667). Anal neuropathy, squeeze pressure, and rectal capacity improved significantly only in the 1 Hz ( P < 0.05) group compared with baseline, but not in other groups. Quality of life domains improved significantly ( P < 0.05) with 1 and 5 Hz groups. No device-related serious adverse events were noted. DISCUSSION: TNT significantly improves FI symptoms in the short term, and the 1 Hz frequency was overall better than 5 and 15 Hz. Both anorectal neuropathy and physiology significantly improved, demonstrating mechanistic improvement. TNT is a promising, novel, safe, efficacious, and noninvasive treatment for FI (see Visual Abstract, Supplementary Digital Content 3, http://links.lww.com/AJG/B598 ).